Regulation of mitochondrial metabolism: Yet another facet in the biology of the oncoprotein Bcl-2 - Krishna, S.; Low, I.; Pervaiz, Shazib (Portland Press Ltd., 2011)
The Bcl-2 (Bcl is B-cell lymphocytic-leukaemia proto-oncogene) family comprises two groups of proteins with distinct functional biology in cell-fate signalling. Bcl-2 protein was the first member to be discovered and associated with drug resistance in human lymphomas. Since then a host of other proteins such as Bcl-xL, Bcl-2A1 and Mcl-1 with similar anti-apoptotic functions have been identified. In contrast, the pro-apoptotic Bcl-2 proteins contain prototypic effector proteins such as Bax and Bak, and the BH3 (Bcl-2 homology)-only proteins comprising Bak, Bid, Bim, Puma and Noxa. A complex interplay between the association of pro-apoptotic and anti-apoptotic proteins with each other determines the sensitivity of cancer cells to drug-induced apoptosis. The canonical functional of Bcl-2 in terms of apoptosis inhibition is its ability to prevent mitochondrial permeabilization via inhibiting the translocation and oligomerization of proapoptotic proteins such as Bax; however, more recent evidence points to a novel mechanism of the anti-apoptotic activity of Bcl-2. Overexpression of Bcl-2 increases mitochondrial oxygen consumption and in doing so generates a slight pro-oxidant intracellular milieu, which promotes genomic instability and blocks death signalling. However, in the wake of overt oxidative stress, Bcl-2 regulates cellular redox status thereby preventing excessive build-up of ROS (reactive oxygen species), which is detrimental to cells and tissues. Taken together, the canonical and non-canonical activities of Bcl-2 imply a critical involvement of this protein in the processes of tumour initiation and progression. In the present paper we review these functionally distinct outcomes of Bcl-2 expression with implications for the chemotherapeutic management of cancers. © The Authors Journal compilation © 2011 Biochemical Society.